Dampak Pembelajaran Online Bagi Peningkatan Kemampuan IT Guru UPT SMK Negeri 3 Muara Enim - Permatasari, Amelia (Yayasan Sembilan Pemuda Indonesia, 2021)
This study aims to determine the impact of online learning experienced by teachers during the Covid-19 pandemic. This research uses quantitative research. The data collection technique was carried out using a survey, which is to find data on relevant matters. The research subjects were teachers of UPT SMKN 3 Muara Enim. The results of this study indicate that online learning has a positive impact on the mastery of Information Technology (IT) teachers at UPT SMK Negeri 3 Muara Enim. The use of many distance learning media has also been tried and used by teachers in delivering teaching materials and materials to students.